2021
DOI: 10.1002/adma.202101150
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Integration of Highly Conductive PdTe2 with Low‐Dimensional Semiconductors for p‐Type Transistors with Low Contact Barriers

Abstract: Low‐dimensional semiconductors provide promising ultrathin channels for constructing more‐than‐Moore devices. However, the prominent contact barriers at the semiconductor–metal electrodes interfaces greatly limit the performance of the obtained devices. Here, a chemical approach is developed for the construction of p‐type field‐effect transistors (FETs) with low contact barriers by achieving the simultaneous synthesis and integration of 2D PdTe2 with various low‐dimensional semiconductors. The 2D PdTe2 synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…[119] More recently, a chemical method to directly synthesize metallic PdTe 2 on the surface of MoTe 2 has been demonstrated by tellurizing a predeposited Pd film at a low temperature. [120] A fine p-type vdW contact to MoTe 2 was achieved, showing a low SBH of 50 meV. Although it is not as good as a transferred vdW contact, the chemical approach is advantageous due to its simple process and great potential for large-scale integration.…”
Section: Transferred 2d Contactsmentioning
confidence: 99%
“…[119] More recently, a chemical method to directly synthesize metallic PdTe 2 on the surface of MoTe 2 has been demonstrated by tellurizing a predeposited Pd film at a low temperature. [120] A fine p-type vdW contact to MoTe 2 was achieved, showing a low SBH of 50 meV. Although it is not as good as a transferred vdW contact, the chemical approach is advantageous due to its simple process and great potential for large-scale integration.…”
Section: Transferred 2d Contactsmentioning
confidence: 99%
“…The suspended PdTe 2 nanoribbons were fabricated on a silicon/silicon dioxide substrate through the eutectic tellurization of Pd thin films under Te vapor at a relatively low temperature of 300 °C. 16 From the scanning electron microscopy (SEM) image and X-ray diffraction (XRD) pattern in Fig. 1, it can be found that the present suspended PdTe 2 nanoribbons have a high crystallinity with a length of 8.89 μm, width of 1.3 μm, and thickness of 136.3 nm.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, a strong magnetic field can reveal the carrier transport mechanism and explore its applicability under strong magnetic field conditions as well as some potential special applications. Based on the realization of the 2D high crystalline PdTe 2 synthesis technology, 16 we prepared suspended PdTe 2 nanoribbons integrated with the probing electrodes, which removed the substrate influence and eliminated the electrical and thermal contact resistances. The electrical resistivity and thermal conductivity were comprehensively measured by applying the direct current heating method at different temperatures up to 14 T, and the influencing mechanism of the magnetic field was studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…This 2D Cu 2 Se structure exhibited a band gap of 0.74 eV, again underscoring that phases distinct from naturally occurring materials can emerge using morphotaxial approaches. Finally, recent work by Zheng et al demonstrated the tellurization of thin Pd films by reacting with Te vapor at 300 °C . The resulting PdTe 2 showed higher conductivity (4.3 × 10 6 S m –1 ) compared to the starting Pd film (3.0 × 10 6 S m –1 ) and also resulted in reduced contact resistances for MoTe 2 and WSe 2 FETs …”
Section: Morphotaxial Anionic Modificationsmentioning
confidence: 99%